PENERAPAN PEMBELAJARAN KOOPERATIF PICTURE AND PICTURE TERHADAP HASIL BELAJAR PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Rialisdiana, Rialisdiana; Ariyati, Eka; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was particularly aimed to reveal the application of cooperative model of Picture and Picture to students’ achievement in classification of living things material of seven grade students of SMP Negeri 12 Pontianak. The form of this study was a quasi-experimental. The design of this study was nonequivalent control group design. Data were collected from two classes; those are VIIB class (experimental group) and VIIA class (Control group). The sample was taken by intact group. The instrument of this study was multiple choice tests. The average of students' achievement of experiment group was 15,2, while the average of students’ achievement of control group was 13,9. the Mann-Whitney U test was obtained Zcount(-2,11) < -Ztable (-1.96), it means that there was a different significant between students’ achievement who taught using cooperative model of Picture and Picture with students’ achievement who taught using conventional model. Keyword: students’achievement, cooperative model of Picture and Picture, classification of living things material.